Screening and brief intervention for lower-risk drug use in primary care: A pilot randomized trial. (1st August 2020) - Bertholet, Nicolas; Meli, Seville; Palfai, Tibor P; Cheng, Debbie M; Alford, Daniel P.; Bernstein, Judith; Samet, Jeffrey H; Lloyd-Travaglini, Christine; Saitz, Richard
Highlights: The efficacy of screening and brief intervention for lower-risk drug use is unknown. This pilot study tested the efficacy of two brief interventions (BIs) for drug use. The study was conducted in primary care patients identified by screening who were followed-up at 6 months. Those assigned to brief intervention reported less drug use than controls. BI was effective in preventing an increase in drug use. Abstract: Aims: The efficacy of screening and brief intervention for lower-risk drug use is unknown. This pilot study tested the efficacy of two brief interventions (BIs) for drug use compared to no BI in primary care patients with lower-risk drug use identified by screening. Methods: We randomly assigned participants identified by screening with Alcohol Smoking and Substance Involvement Screening Test (ASSIST) drug specific scores of 2 or 3 to: no BI, a brief negotiated interview (BNI), or an adaptation of motivational interviewing (MOTIV). Primary outcome was number of days use of main drug in the past 30 as determined by validated calendar method at 6 months. Analyses were performed using negative binomial regression adjusted for baseline use and main drug. Results: Of 142 eligible adults, 61(43 %) consented and were randomized. Participant characteristics were: mean age 41; 54 % male; 77 % black. Main drug was cannabis 70 %, cocaine 15 %, prescription opioid 10 %; 7% reported injection drug use and mean days use of main drug (of 30) was 3.4. At 6 months, 93 % completed follow-up and adjusted mean days use of main drug were 6.4 (no BI) vs 2.1 (BNI) (incidence rate ratio, IRR 0.33[0.15−0.74]) and 2.3 (MOTIV) (IRR 0.36[0.15−0.85]). Conclusions: BI appears to have efficacy for preventing an increase in drug use in primary care patients with lower-risk use identified by screening. These findings raise the potential that less severe patterns of drug use in primary care may be uniquely amenable to brief intervention and warrant replication.